Analisis Respon dan Faktor-Faktor yang Mempengaruhi Permintaan Beras Indonesia - Dudi Septiadi; Umbu Joka (AGRIMOR, 2019)
This study aims to 1) analyze the factors that influence the demand for Indonesian rice, and 2) analyzing the response to rice demand from the factors that influence it. The data in this study use time series data for the period 1988-2017. Data analysis using linear regression analysis method. The results showed that Indonesian rice demand was influenced by retail rice prices, per capita income, population, rice production and Indonesian rice demand lag at α level of 5 percent with an R-Squared value of 91.3 percent. Based on the analysis of responses, the population number variable is the only independent variable that has elastic elasticity (E> 1) both in the short and long term analysis. Variable retail rice prices, per capita income and rice production, have elasticity values ​​that are inelastic (E <1) in both the short and long term analysis.